Cell Line Techniques and Gene Editing Tools for Antibody Production: A Review - Dangi, Arun K.; Sinha, Rajeshwari; Dwivedi, Shailja; Gupta, Sanjeev K.; Shukla, Pratyoosh (Frontiers in Pharmacology, 2018)
The present day modern formulation practices for drugs are based on newer tools and techniques towards effective utilization. The methods of antibody formulations are to be revolutionized based on techniques of cell engineering and gene editing. In the present review, we have discussed innovations in cell engineering towards production of novel antibodies for therapeutic applications. Moreover, this review deciphers the use of RNAi, ribozyme engineering, CRISPR-Cas-based techniques for better strategies for antibody production. Overall, this review describes the multidisciplinary aspects of the production of therapeutic proteins that has gained more attention due to its increasing demand.